Relationship of seat location, approaches to learning, and academic performance of second year medical students. - Guerrero, Margarita DLR
Student's seat location has been examined as a physical variable in large classes in relation to personality variable and academic performance. Researches regarding the relationship of seat location and personality indicate strong evidence to link the two. However, studies regarding the relationship of seat location and academic performance show conflicting evidences prompting authors to recommend search for factors that may further explain the relationship between these two variables. This correlation study examined a third variable, students' approaches to learning, as a possible mechanism that mediates between seat location and academic performance. The objectives were: 1) to determine students' final seat location and approaches to learning; 2) To determine the relationship between seat locations, approaches to learning and academic performance. The study took place in one private Catholic sectarian medical school, with a discipline-based type of curriculum. The population of the study included fifty two second year students enrolled in one of seventeen courses offered during the second year of medical education, for academic year 2013-2014. The period of the study was the first module (introductory module), with a total of five class sessions. The class met for two hours once a week in a large classroom with seats arranged in traditional rows-and-columns. Seat location was divided into four areas based on proximity to the front of the classroom. Students were allowed free choice of seat location for all five lecture sessions. Students were asked to fill out a seat map for each of the five class meeting, and the final seat map was drawn after the last meeting. Student's final seat location was defined as the area which a student seats most frequently (three out of five). Students approaches to learning was determined using the Revised 2-Factor Study Process Questionnaire by Biggs administered during the last class meeting. Academic performance was defined as students' score (quality point index) in the module exam which was given one week after the last class meeting. Descriptive data was presented using means and standard deviations. Chi square was used to determine the final seat location and approaches to learning. ANOVA was used to determine if academic performance varied according to seat location and approaches to learning. As seat location went farther from the front, there was increase in number of surface learners. Seat location was associated with academic performance. Students seated nearer the front of the classroom had better academic performance compared to those seated farther. Statistical evidence indicated that neither did nor surface approach was associated with better academic performance. The study concluded that in this large class of second year medical students, seat location is associated with academic performance.